Jean Toomer : race, repression, and revolution - Foley, Barbara, 1948- (University of Illinois Press, 2014)
"The 1923 publication of Cane established Jean Toomer as a modernist master and one of the key literary figures of the emerging Harlem Renaissance. Though critics and biographers alike have praised his artistic experimentation and unflinching eyewitness portraits of Jim Crow violence, few seem to recognize how much Toomer's interest in class struggle, catalyzed by the Russian Revolution and the post-World War One radical upsurge, situate his masterwork in its immediate historical context. In Jean Toomer: Race, Repression, and Revolution, Barbara Foley explores Toomer's political and intellectual connections with socialism, the New Negro movement, and the project of Young America. Examining his rarely scrutinized early creative and journalistic writings, as well as unpublished versions of his autobiography, she recreates the complex and contradictory consciousness that produced Cane. Foley's discussion of political repression runs parallel with a portrait of repression on a personal level. Examining family secrets heretofore unexplored in Toomer scholarship, she traces their sporadic surfacing in Cane. Toomer's text, she argues, exhibits a political unconscious that is at once public and private."--